Determinants of customer awareness towards insurance products in MCIS Zurich Melaka / Nur Azean Sholehah Aziz - Aziz, Nur Azean Sholehah (2011)
This research is about the level of customer awareness towards insurance product in MCIS Zurich. The independent variable such as choice of media, quality of products, campaign and intermediaries, are being identify in order to make an investigated whether or not these independent have significant and influenced the customer awareness towards insurance products. This research was conducted in Melaka’s area where 50 questionnaires were distributed and 50 questionnaires were returned. In order to obtain the data, the researcher was used two methods that are primary and secondary data. Data analyzed using reliability test, frequency analysis, descriptive statistics and backward elimination method. Based on the analysis, the result showed that campaign is the most contribute factor that customer awareness towards insurance products in MCIS Zurich Melaka branch. Zurich Melaka branch.